2005
DOI: 10.1002/adma.200500863
|View full text |Cite
|
Sign up to set email alerts
|

Bioassisted Room‐Temperature Immobilization and Mineralization of Zinc Oxide—The Structural Ordering of ZnO Nanoparticles into a Flower‐Type Morphology

Abstract: tate and methyl benzoate (90:10 w/w) and used for the thickness-period library. Different amounts of this mixture were dispensed using a micropipette (Brand Transferpette) in the different columns. Solvent was evaporated under ambient conditions. Thicknesses were characterized using a stylus profilometer (Dektak 3M). The same mixture of solvents was used for the composition-period libraries.The exposure was performed using an USHIO lithographic system (filter at 365 nm, intensity 5 mW cm -2 ). After exposure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
194
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(203 citation statements)
references
References 26 publications
(12 reference statements)
4
194
0
3
Order By: Relevance
“…Crystalline ZnO could not be grown on the triple helix at high pH without ZnO-1 peptide, and it indicates that the ZnO-1 peptide catalyzes the growth of single crystalline ZnO under these extreme conditions. Previously, Umetsu et al 72 reported that cysteine in the GGGSC tag of the ZnO-1 peptide was required to grow flower-like ZnO microparticles at room temperature, and the combination of this GGGSC tail and the rest of the amino acid residues, EAHVMHKVAPRP, is likely to be important in the growth of single crystalline ZnO nanowires at low temperature and pH 10.0; at pH 10.0, cysteine is negatively charged and this negative charge recruits positive zinc ions onto the template nanowires efficiently. Then, the basic amino-acid-dominant EAHVMHKVAPRP part could produce local pH and charge distributions at the molecular level that favor the condensation of the intermediates and catalyze the dehydration to produce ZnO.…”
Section: Genetically Modified Collagen-like Triple Helix Peptidementioning
confidence: 96%
See 2 more Smart Citations
“…Crystalline ZnO could not be grown on the triple helix at high pH without ZnO-1 peptide, and it indicates that the ZnO-1 peptide catalyzes the growth of single crystalline ZnO under these extreme conditions. Previously, Umetsu et al 72 reported that cysteine in the GGGSC tag of the ZnO-1 peptide was required to grow flower-like ZnO microparticles at room temperature, and the combination of this GGGSC tail and the rest of the amino acid residues, EAHVMHKVAPRP, is likely to be important in the growth of single crystalline ZnO nanowires at low temperature and pH 10.0; at pH 10.0, cysteine is negatively charged and this negative charge recruits positive zinc ions onto the template nanowires efficiently. Then, the basic amino-acid-dominant EAHVMHKVAPRP part could produce local pH and charge distributions at the molecular level that favor the condensation of the intermediates and catalyze the dehydration to produce ZnO.…”
Section: Genetically Modified Collagen-like Triple Helix Peptidementioning
confidence: 96%
“…4,69 Using the same strategy as in the case of the Au coating, a synthetic peptide, ZnO-1 (Glu-Ala-His-Val-Met-His-Lys-Val-Ala-Pro-Arg-Pro-Gly-Gly-Gly-Ser-Cys), which has a high affinity for ZnO crystals and catalyzes ZnO growth at low temperature, was attached to the F877 template via hydrogen bonding. 69,72 This ZnO-1 peptide-coated F877 triple helix was used for the ZnO nanowire growth. When zinc acetate was hydrolyzed on the ZnO-1 peptide-coated triple helix at pH 10.0 at 4 C for 9 days, ZnO nanowires were obtained from the supernatant of the growth solution via centrifugation, as shown in Figure 9.9a.…”
Section: This Chapter Has Been Retractedmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the widespread speculations propose that a few enzymes or peptides present in the organic matrix (mainly in cell walls and periplasmic space) act as reducing and nucleation sites (Mukherjee et al, 2001;Ahmad et al, 2002;Dameron et al, 1989;Umetsu et al, 2005;Kröger et al, 2006;Naik et al, 2002), the molecular basis for the biosynthesis of these materials is not well established. Currently, there are two main directions of research in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The tactic of this method is to isolate the peptides that bind specifically to a target from a random peptide library, which displays peptides of 10 9~1 0 10 variants on the tip of the minor protein pIII of a filamentous phage named M13 16,17) . A simple method allowing the creation of peptides without immunization of animals, the phage display method has recently been utilized not only for organic materials [18][19][20][21][22] , but also for several inorganic materials 12,[23][24][25][26][27][28][29] . However, a peptide that binds to zirconia has yet to be identified.…”
Section: Introductionmentioning
confidence: 99%